Multiparametric Magnetic Resonance Imaging in the Diagnosis of Clinically Significant Prostate Cancer: an Updated Systematic Review. Issue 12 (December 2021) - Haider, M.A.; Brown, J.; Yao, X.; Chin, J.; Perlis, N.; Schieda, N.; Loblaw, A.
Abstract: There has been growing utilisation of multiparametric magnetic resonance imaging (MPMRI) as a non-invasive tool to diagnose and localise clinically significant prostate cancer (CSPCa). This updated systematic review examines the use of MPMRI in patients with an elevated risk of CSPCa who have had a prior negative transrectal ultrasound systematic biopsy (TRUS-SB) and who were biopsy naïve. MEDLINE, EMBASE and the Cochrane Database of Systematic Reviews were searched for existing systematic reviews published up to September 2020. The literature search of the electronic databases combined disease-specific terms (prostate cancer, prostate carcinoma, etc.) and treatment-specific terms (magnetic resonance, etc.). Studies were included if they were randomised controlled trials (RCTs) comparing MPMRI to template transperineal mapping biopsy (TPMB) or to TRUS-SB. Thirty-six RCTs were eligible. For biopsy-naïve men, accuracy of diagnosis of CSPCa showed sensitivities from 87 to 96% and specificities ranging from 29 to 45%. Meta-analyses for CSPCa showed increased detection favouring MPMRI-targeted biopsy over TRUS-SB by 3% (95% confidence interval 0–7%, P = 0.03) and decreased detection of clinically insignificant prostate cancer (CISPCa) favouring MPMRI by 8% (95% confidence interval –11 to 5%, P < 0.00001). Accuracy of MPMRI for men with prior negative biopsy showed sensitivities of 78–100% and specificities of 30–100%. Meta-analyses comparing MPMRI to TRUS-SB showed increased detection of 5% (95% confidence interval 3–7%, P < 0.0001) with a reduction of CISPCa detection of 7% (95% confidence interval 4–9%, P < 0.00001). The growing acceptance of MPMRI utilisation internationally and the recent publication of several RCTs regarding MPMRI in reducing CISPCa detection rates, particularly in biopsy-naïve men, without loss of sensitivity for CSPCa necessitates the synthesis of updated evidence examining MPMRI in the diagnosis of CSPCa. Highlights: For biopsy naïve men MPMRI has an accuracy of diagnosis of CSPCa from 87% to 96% and specificities ranging from 29% to 45%. For biopsy naive men, meta-analyses shows increased detection of CSPCa by MPMRI-TB over TRUS-SB by 3% (95% CI, 0%–7%, p = 0.03) and ecreased detection of CISPCa by MPMRI of 8% (95% CI, -11%–5%, p < 0.00001). For men with prior negative biopsy for prostate cancer MPRI shows sensitivities of 78%–100% and specificities of 30%–100%. For men with prior negative biopsy, meta-analyses comparing MPMR to TRUS-SB showed 5% increased CSPCa detection (95% CI, 3%-7%, p < 0.0001) and 7% reduced CISPCa detection (95% CI, 4%-9%, p < 0.00001)